Intra-industry trade and innovation: An empirical study of the Colombian manufacturing industry (2001)
This paper analyses the theoretical and empirical relationship between intra-industry trade (IIT) flows in manufactures and technical change for the Colombian manufacturing industry during the 1970-95 period. A general estimating equation for the sources of change of the equilibrium number of varieties, in which TFP growth is one of its components, is derived from the basic model of trade in differentiated goods with monopolistic competition. Based on that relationship, several estimations on the determinants of IIT flows are carried out. The econometric set up follows a panel data and cross-section estimations of system of simultaneous equations. TFP and IIT indices are the endogenous variables of the system with industry characteristic, trade policy, and innovation-activity variables as the set of exogenous variables. The paper also presents a comparative analysis in the direction and trends of Colombia's IIT flows in manufactures with the Group of Seven, NAFTA, and the Latin American Free Trade area members (LAFTA) since 1974.